Hello dear
4x^2-4x-5=0
● Step 1
if F(y) = ax^2 + bx + c
∆ = b^2 - 4(a)(c) & ∆ ≥ 0
F(x) = 4x^2-4x-5
a = +4 , b = -4 , c = -5
∆ = (-4^2) - 4 (4)(- 5)
∆ = 16 + 80
∆ = 96 ≥ 0
● Step 2
x = [ -b ± √ ∆ ] / 2a
{ √ 96 = √ (16 * 6 ) = 4 √ 6 )
x1 = [ -b + √ ∆ ] / 2a = [ -(-4) + 4 √ 6 ] / 2(4) = [ 4/8] + [ 4 √ 6 / 8 ]
x1 = 1/2 + 1/2 √ 6 = 1/2( 1 + √ 6)
x2 = [ -b - √ ∆ ] / 2a = [ -(-4) - 4 √ 6 ] / 2(4) = [ 4/8] - [ 4 √ 6 / 8 ]
x2 = 1/2 - 1/2 √ 6 = 1/2( 1- √ 6)
so
x 1 = -0.724745
x 2 = 1.72474
Good Luck Darling ♣
2006-10-31 11:00:28
·
answer #1
·
answered by sweetie 5
·
6⤊
0⤋
4x^2 - 4x - 5 = 0
is of the form ax^2 + bx + c
where a = 4, b = -4 and c = -5
Plugging these into x = [-b ± sqrt(b^2 - 4ac)] / (2a) gives :
x = {-(-4) ± sqrt[(-4)^2 - 4(4)(-5)} / (2 * 4)
= [4 ± sqrt(16 +16 * 5)] / 8
= [4 ± sqrt(16 * 6)] / 8
= [4 ± 4 * sqrt(6)] / 8
= [1 ± sqrt(6)] / 2
The 2 solutions are : [1 - sqrt(6)] / 2 , [1 + sqrt(6)] / 2
2006-10-31 08:05:29
·
answer #2
·
answered by falzoon 7
·
0⤊
0⤋
Do you know the quadratic formula?
All you do is plug in 4 for a, -4 for b and -5 for c and simplify.
x=(4+/-sqrt(96))/8 which simplifies to
(1+sqrt6)/2 and (1-sqrt6)/2
Sorry, but my computer doesn't have the square root symbol
2006-10-31 07:52:38
·
answer #3
·
answered by Melody 3
·
0⤊
0⤋
the quadratic formula is used to medical care the a wager variable ideas in quadratic equations, that are equations wherein the a variable is squared. the formula itself is: x = -b (+/-) (sq. root of (b^2-4ac) / 2a so given 2x^2 +9x + 4 a= 2 b= 9 c= 4 so then plugging it into the equation: x= (-9) (+/-) sq. root (9^2-4(2) (4) / 2(2) simplified: x= -9 (+/-) sq. root (40 9) / 4 x= (-9 + 7)/ 4 or (-9 - 7) /4 solved: x = -a million/2, or -4 choose that facilitates! stable achievement...
2016-12-28 09:04:15
·
answer #4
·
answered by santolucito 3
·
0⤊
0⤋
x=5/4x^2-4
2006-10-31 07:47:48
·
answer #5
·
answered by crussel4 2
·
0⤊
1⤋
4x^2-4x-5=0
=> (2x)^2 - 2(2x) - 5 = 0
Let 2x=y
y^2-2y-5=0
=> (y-sqrt(5)) = 0
=> y = sqrt(5)
=> 2x = sqrt(5)
hence x = sqrt(5) / 2
2006-10-31 07:54:38
·
answer #6
·
answered by Manisha 4
·
0⤊
1⤋
x=
(-1+ sqrt 6)/2
(-1 - sqrt 6)/2
2006-10-31 07:49:25
·
answer #7
·
answered by sjv_ch 1
·
0⤊
0⤋
4x^2-4x-5=0
x=(4+/-sqrt(16+4+4+5))/8=.5+/-sqrt(96)/8
x=.5+/-.5sqrt(6)
x=.5(1+/-sqrt(r)=1.725, -.725
2006-10-31 07:50:03
·
answer #8
·
answered by yupchagee 7
·
0⤊
1⤋